HUBUNGAN PAPARAN SIARAN TRAXGRADE YOUR AWARENESS DI RADIO 90.2 TRAX FM SEMARANG TERHADAP PENGETAHUAN MENGENAI HIV AIDS PADA SISWA SMAN 1 KOTA SEMARANG - Ikra Andita Maharsetia; Tinuk Istiarti; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2016)
Health promotion can’t be separated from the media, and radio is one of the electronic media that is close to the community. Communication, information and education on the radio is expected to increase knowledge of adolescents about HIV AIDS. The purpose of this study was to analyze the relationship of Radio Trax FM 90.2 Semarang broadcast exposure to knowledge about HIV AIDS at the 11th grade high school students of SMAN 1 Semarang.This type of research is descriptive analytic with cross sectional approach. The research sample was calculated by the formula slovin and obtained a sample of at least 140 respondents. Data were analyzed by univariate using frequency distribution table and bivariate using cross tabulation and analysis of the relationship using chi-square test.The results showed 75.7% of respondents were 16 years old, 61.4% of respondents were female and 77.1% of respondents are not used to listening to the radio. For the correlation test showed no correlation between, the understanding of the health messages () and the acceptance of the health messages () with knowledge about HIV AIDS. To improve knowledge about HIV AIDS through radio, Trax FM 90.2 radio Semarang is advised to provide a health education every month.